Implementasi Trauma Healing dan Pendidikan Lingkungan Pada Anak-Anak Pasca Bencana Banjir di Kota Palangka Raya - Kukuh Wurdianto; Liberti Natalia Hia; Evi Fitriana; Muhammad Dwi Toriyono; Muhamad Khoiri Ridlwan (Universitas Sarjanawiyata Tamansiswa, 2022)
The incidence of disasters increased in Indonesia. Most of these disasters are environmental disasters such as hurricanes, floods and landslides. Massive flooding occurred in several districts in Central Kalimantan in November 2021. Based on data from the BPBD of Palangka Raya City, it was recorded that 31,013 residents consisting of 8,876 families became victims of the flood. In addition to the physical impact, the psychological impact after the flood disaster needs to be considered. The psychological impact that occurs is in the form of anxiety, stress and trauma to the victims. Trauma to victims of natural disasters cannot be allowed to drag on so that disaster victims can continue their normal lives, therefore trauma recovery/trauma healing is needed. Especially for school-age children, trauma healing is carried out using a pedagogical approach. The pedagogical approach used refers to the pattern of development and education that is being experienced by victims, especially children, so that the trauma healing process can run and have an effect as expected. In addition to post-disaster trauma recovery, there is also a need for environmental education that has a role in preventing and reducing the risk of environmental disasters. Environmental education must facilitate various learning processes on cognitive and awareness aspects, attitudes and behavior, and collective action to institutionalize environmentally friendly and disaster-sensitive behavior.